Physical Model of Water Seepage Through Porous Medium (Proceedings of Faculty of Civil Engineering, 2019)
This paper describes basic principles and governing equations for describing groundwater flow through porous material. In order to obtain the relevant values of some of the characteristic physical quantities of groundwater flow in the sandy porous material (infiltration velocity, equipotential at a certain point within the space, hydraulic gradients, flow, etc.), the physical model GUNT HM169 was used, which is an integral part of the hydro technical laboratory of the Faculty of Civil Engineering, University of Rijeka. The paper describes the working principle for the mentioned physical model and the preparation of the experimental trials themselves. In this respect, several hydrodynamic analyzes of groundwater flow regarding the upper and lower water variability potential were made as well as the flow analysis below the vertical steel diaphragm and the analysis of groundwater depletion under the spatially trapezoidal modified natural sloping dam. To carry out the experiment, the sloping dam was manually made of Plexiglas. The purpose of the research through the physical model HM169 was to obtain a clearer picture of the streamline field below the individual hydroelectric objects and consequently to obtain a simulation of the propagation of the groundwater flow which was followed by a yellow fluorescence tracer.
Keywords: water infiltration; Darcy’s speed; potential flow; equipotential network; hydraulic gradient; physical model; hydraulic analysis